Applied Microsoft business intelligence - Leblanc, Patrick (Indianapolis, Indiana : John Wiley & Sons, Inc., 2015)
Thi book shows how to leverage the complete set of Microsoft tools including Microsoft Office and SQL Server to better analyze business data. It provides best practices for building complete BI solutions using the full Microsoft toolset. Topics include: how to effectively use SQL Server Analysis and Reporting Services, along with Excel, SharePoint, and other tools to provide effective and cohesive solutions for the enterprise; BI architecture; data queries; semantic models; multidimensional modeling; data analysis and visualization; performance monitoring; data mining; practical business analysis and reporting. --
Part I: Overview of the Microsoft Business Intelligence Toolset. Which Analysis and Reporting Tools Do You Need? -- Designing an Effective Business Intelligence Architecture -- Selecting the Data Architecture that Fits Your Organization -- Part II: Business Intelligence for Analysis. Searching and Combining Data with Power Query -- Choosing the Right Business Intelligence Semantic Model -- Discovering and Analyzing Data with Power Pivot -- Developing a Flexible and Scalable Tabular Model -- Developing a Flexible and Scalable Multidimensional Model -- Discovering Knowledge with Data Mining -- Part III: Business Intelligence for Reporting. Choosing the Right Business Intelligence Visualization Tool -- Designing Operational Reports with Reporting Services -- Visualizing Your Data Interactively with Power View -- Exploring Geographic and Temporal Data with Power Map -- Monitoring Your Business with PerformancePoint Services -- Part IV: Deploying and Managing the Business Intelligence Solution. Implementing a Self-Service Delivery Framework -- Designing and Implementing a Deployment Plan -- Managing and Maintaining the Business Intelligence Environment -- Scaling the Business Intelligence Environment.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Business intelligence -- Computer programs; Business planning; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Electronic books; Electronic books